Investigation of Factors Affecting the Six‐Minute Walk Test Results in Hemodialysis Patients. Issue 6 (27th March 2014) - Kono, Kenichi; Nishida, Yusuke; Moriyama, Yoshihumi; Yabe, Hiroki; Taoka, Masahiro; Sato, Takashi
Abstract Renal anemia, uremic myopathy, and malnutrition are some of the factors that affect the results of the 6‐minute walk test (6MWT) in hemodialysis patients. We hypothesized that skeletal muscle dysfunction caused by skeletal myolysis, protein hypercatabolism, and mitochondrial deficiency are strongly related factors. The purpose of this study was to clarify the factors that affect the 6MWT results in hemodialysis patients to assess their exercise tolerance. The study included 43 outpatients from the hemodialysis unit. The 6MWT was performed, and knee extension strength, 1‐leg standing time, and grip were measured. In addition, the subjects' characteristics such as age, preexisting coronary artery disease, hemoglobin level, total iron binding capacity, serum albumin level, creatinine generation rate, and normalized protein catabolic rate were investigated. A stepwise multiple regression model was used to examine the factors affecting the 6MWT results. Multiple regression analysis revealed that knee extension strength (β = 0.446, P = 0.001), total iron binding capacity (β = −0.299, P = 0.021), and preexisting coronary artery disease (β = −0.272, P = 0.035) significantly affected the 6MWT results (R = 0.66, R2 = 0.44). The 6MWT in hemodialysis patients was strongly affected by muscle strength, iron deficiency anemia, and preexisting coronary artery disease, suggesting that resistance training is important for improving 6MWT results. Our findings indicate that iron deficiency and cardiac function should be assessed before exercising or undergoing an exercise tolerance test.